[Husavik, Iceland] - Streng, Evelyn Fiedler (1975)
Photograph of Husavik, Iceland. White and grey, rectangular buildings sit along a grassy hill in the distance. A rock and boat lined harbor walkways sit in the grey water in the middle ground, curving from the land surround it. A long, blue buildings sits along the harbor to the left.